The Relationship Between Emotional Intelligence and Students’ Academic Engagements at University Level - Abbas, Muhammad Ghazanfar; Safdar Ali, Faiza; Shah, Dr. Muhammad Anees ul Husnain (Al-Aijaz Research Journal of Islamic Studies & Humanities, 2025)
Present study was planned to investigate “The relationship between emotional intelligence and academic engagement of students at university level”. The study was delimited to Bhakkar, Mianwali and Sargodha main campus of university of Sargodha. Due to shortage of time the sample was delimited up to 1000 students of university level. One scale use to measure the emotional intelligence of the students with 33 items and four factors and other scale of students’ academic engagement with 15 items and three factors. Objectives of the study were (a) to measure the level of emotional intelligence of students at university level; (b) measure the level of academic engagement of students at university level; (c) find out the gender differences in the phenomenon of emotional intelligence academic engagement of students at university level; (d) Investigate the relationship between emotional intelligence and academic engagement of students at university level. The data were analyzed by using Statistical Package for Social Sciences (SPSS). The score thus obtained was analyzed by using t-test, mean score and Pearson r. Results indicated that students show good level of emotional intelligence exhibit good level of academic engagement at university level. Although there were many limitations of the study even then findings are found acceptable according to the age and grade level of students.